2020
DOI: 10.1108/yc-05-2020-1148
|View full text |Cite
|
Sign up to set email alerts
|

Examining the importance of gamification, social interaction and perceived enjoyment among young female online buyers in India

Abstract: Purpose The current research has dual motives. Firstly, this study aims to evaluate the effect of gamification on the behavioural intention (BI) of the young female consumers to use online websites for making purchases. Secondly, it examines the role of social interaction and perceived enjoyment (PE) – two antecedents that are considered to have an impact on the female buying behaviour in e-commerce. Design/methodology/approach A model is developed based on the technology acceptance model. The conceptual fra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
37
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(57 citation statements)
references
References 113 publications
3
37
1
1
Order By: Relevance
“…Therefore, the result found that symmetric social interaction has a positive significant impact on use context and perceived enjoyment. The outcome of this relationship is supported by Reference [70]. Another relation, i.e., use context, has found to have an impeccable effect on perceived enjoyment and perceived ease of use, which is supported by Reference [57].…”
Section: Discussionmentioning
confidence: 66%
“…Therefore, the result found that symmetric social interaction has a positive significant impact on use context and perceived enjoyment. The outcome of this relationship is supported by Reference [70]. Another relation, i.e., use context, has found to have an impeccable effect on perceived enjoyment and perceived ease of use, which is supported by Reference [57].…”
Section: Discussionmentioning
confidence: 66%
“…Gamification elements are also determined in the form of examples and taxonomies (Liu et al , 2017). Examples include the use of points, leaderboards, progress bar, badges and videos, as achievement systems used by several researchers such as Raman (2020); Cheong et al (2014); and Koivisto and Hamari (2014). One such taxonomical classification is the mechanics, dynamics and aesthetics (MDA) framework (Hunicke et al , 2004).…”
Section: Resultsmentioning
confidence: 99%
“…A study by Raman ( 2020 ) found that perceived enjoyment positively influences purchase intention. Verhagen and Van Dolen ( 2011 ) mentioned that, to increase income and customer maintenance, online retailers should focus on perceived enjoyment.…”
Section: Research Model and Hypothesis Developmentmentioning
confidence: 99%